FAKTOR YANG MEMENGARUHI MANAJEMEN LABA DENGAN MODERASI CORPORATE GOVERNANCE - Justin, Justin; Tanusdjaja, Hendang (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the effect of firm size, financial distress, and leverage on earnings management moderated by corporate governance. The sample used in this study was taken by purposive sampling method from companies listed on the IDX during 2018-2020. The data is secondary data and processed using SPSS version 25 and Microsoft Excel 2019. Based on the criteria, 54 companies were selected that could be used as samples. The total number of data is 162 minus 40 outlier data so that the amount of data that can be used is 122 data and then tested with multiple linear regression analysis technique. Based on the research conducted, firm size and financial distress have a significant positive effect on earnings management, while leverage has no effect on earnings management. Corporate governance with independent commissioners as a proxy cannot moderate firm size and financial distress, but can moderate the relationship between leverage and earnings management.